The Implementation of Working Parents' Parenting Patterns in Fostering Independence in Four-Year-Old Children - Ayu Denisa; Fitri Ayu Fatmawati; Mushab Al Umairi (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Early childhood is a golden age during which brain development progresses rapidly, making appropriate parenting patterns essential for fostering independence from an early age. This study aims to identify the forms of parenting and daily habituation implemented by working parents in developing children’s independence, as well as to explore the challenges encountered in this process. The research employed a descriptive qualitative approach with a case study design, involving a four-year-old girl and one parent as respondents. Data were collected through interviews, observations, and documentation. The findings show that working parents are still able to nurture their child’s independence through consistent application of democratic parenting. Parents provided opportunities for the child to make simple decisions, complete tasks independently, and participate in age-appropriate household activities. Habituation practices such as tidying up belongings, choosing toys, and helping with small household chores were found to strengthen the child’s sense of responsibility and self-regulation skills. In addition, warm communication, positive role modeling, and clear boundaries helped the child understand rules without experiencing pressure. Challenges mainly stemmed from the parents’ limited time due to work commitments; however, these obstacles were addressed through effective time management and prioritizing quality interactions. These findings reinforce that democratic parenting is effective in fostering children’s independence, even among parents with demanding work schedules.